The Style of the Second Letter of Peter - Callan, Terrance (Biblica, 2003)
Readers of the Second Letter of Peter have often commented on its style, usually in negative terms. This essay examines the style of 2 Pet more thoroughly than has been done heretofore, using Cicero’s discussion of style, and that of other ancient writers, as a framework. This examination shows that 2 Pet largely conforms to ancient canons of style and should be seen as an example of the grand Asian style. Recognition of this may help readers avoid unthinking assessment of 2 Pet’s style by standards not accepted by its author, and develop greater appreciation of its style in terms of its author’s own aims and standards.